Emotional Prosodies Processing and Its Relationship With Neurodevelopment Outcome at 24 Months in Infants of Diabetic Mothers - Sun, Guoyu; Liu, Yanan; Zhang, Rui; Peng, Cheng; Geng, Yuehang; Zhou, Faliang; Hou, Xinlin; Liu, Lili (Frontiers in Pediatrics, 2022)
Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy. Hyperglycemia of pregnancy is a risk not only for later obesity of the offspring but also do harm to their neurodevelopment from fetus. An ERP research has shown that children with autism spectrum disorder (ASD) was characterized by impaired semantic processing. In this study, we used event-related potential (ERP) to assess the procession of different emotional prosodies (happy, fearful, and angry) in neonates of diabetic mothers, compared to the healthy term infants. And to explore whether the ERP measure has potential value for the evaluation of neurodevelopmental outcome in later childhood. A total of 43 full-term neonates were recruited from the neonatology department of Peking University First Hospital from December 1, 2017 to April 30, 2019. They were assigned to infants of diabetic mothers (IDM) group (n = 23) or control group (n = 20) according to their mother’s oral glucose tolerance test’s (OGTT) result during pregnancy. Using an oddball paradigm, ERP data were recorded while subjects listened to deviation stimulus (20%, happy/fearful/angry prosodies) and standard stimulus (80%, neutral prosody) to evaluate the potential prognostic value of ERP indexes for neurodevelopment at 24 months of age. Results showed that 1) mismatch response (MMR) amplitudes in IDM group were lower than the control; 2) lower MMR amplitude to fearful prosody at frontal lobe was a high risk for increased Modified Checklist for Autism in Toddlers (M-CHAT) scores at 24 months. These findings suggests that hyperglycemia of pregnancy may influence the ability to process emotional prosodies in neonatal brain; it could be reflected by decreased MMR amplitude in response to fearful prosody. Moreover, the decreased MMR amplitude at the frontal lobe may indicated an increased risk of ASD.